Unobservable effects and speed of adjustment to target capital structure - Matemilola, Bolaji Tunde; Amin Noordin, Bany Ariffin; Wan Ngah, Wan Azman Saini; Md Nassir, Annuar (Universiti Malaysia Sarawak, 2015)
The paper investigates whether unobservable firm-specific effects such as managerial ability is a major component of the target capital structure. We apply the system generalized method of moments that accounts for unobservable firm-specific effects. Our results reveal that unobservable firm-specific effects such as managerial ability are a major component that explains most of the cross-sectional variation in firms’ capital structure in Malaysia.